Extracellular matrix-inspired BMP-2-delivering biodegradable fibrous particles for bone tissue engineering. Issue 42 (24th September 2015) - Shin, Young Min; La, Wan-Geun; Lee, Min Suk; Yang, Hee Seok; Lim, Youn-Mook
Abstract : A heparin conjugated fibrous particle resembling the structure of an extracellular matrix was developed. The BMP-2 loaded particles promoted osteogenic differentiation and healing of a bone defect, in vitro and in vivo . Abstract : Growth factors have been used to regenerate specific tissue structures by stimulating proliferation and migration of target cells, as well as regulating differentiation of various stem cells. To improve tissue regeneration, growth factors need effective delivery carriers to effect their long-term and sustained release to the target region. For this reason, we fabricated a valuable growth factor delivery carrier termed fibrous particles (FPs) with a morphology similar to that of the extracellular matrix (ECM). These FPs were prepared by aminolysis of poly(l -lactic acid) nanofibrous sheets and modified for sustaining growth factor delivery by heparinization (to produce Hep-FPs). We confirmed that Hep-FPs showed stable bone morphogenetic protein-2 (BMP-2) binding and sustained BMP-2 releasing. In addition, the released BMP-2 from the Hep-FPs successfully improved alkaline phosphatase activity and mineralization of human mesenchymal stem cells in vitro . To demonstrate the effect of bone regeneration using the BMP-2 delivery carrier, we implanted FPs, Hep-FPs, FPs-BMP-2, and Hep-FPs-BMP-2 onto a critically sized region of a mouse calvarial defect (∅ 4 mm). After 8 weeks of treatment, Hep-FPs-BMP-2 exhibited broader new bone formation and much higher bone density at the defect area than did the other particles. Therefore, FPs resembling the ECM can be used as an instructive tool for a variety of tissue regeneration purposes.